Diffuse Borders . Notes on the rise of special indigenous jurisdiction in Colombia and its relationship to state law (2008)
This article analyzes three circunstances that have accompanied the beginning of Colombian Indigenous Special Jurisdiction. First, the transition from an unitary conception of nation to one multicultural. Second, the process of reconstruction of indigenou